Is urbanization eco-friendly? An energy and land use cross-country analysis. (January 2017) - Long, X.; Ji, Xi; Ulgiati, S.
Abstract: Urbanization imposes complicated and heterogeneous impacts on ecosystems. With the purpose of reflecting the comprehensive influence of urbanization on the ecosystem, we choose the ecological footprint to represent the ecosystem's integrated change and distinguish low-income, middle-income and high-income countries to reflect the nonlinear impact. This paper uses both static and dynamic STIRPAT (Stochastic Impacts by Regression on Population, Affluence and Technology) models to analyze 72 countries at different income levels during the 1980–2008 period. The results show that the overall ecological elasticity of urbanization at the global level is negative. Specifically, results suggest urbanization, associated to increased income, to have eco-friendly potential in terms of decreased ecological footprint. To explain such results, this paper answers two questions: Why does urbanization show ecological protection effects? Why does a more pronounced protection effect seem associated to increased income levels? Improved market mechanism, increased resource use efficiency as well as increased environmental awareness in urban areas associated to increased income levels are likely to support an eco-friendly urbanization process. Burden-shift to low-income countries also needs to be taken into account, in order to avoid policies that increase wellbeing locally at the expenses of far-away areas. Highlights: Ecological effects of urbanization are estimated. Ecological footprint is used to represent the integrated change related to energy and land use. Static and dynamic STIRPAT models are employed for regression. The reasons for the ecological protection effect of urbanization are analyzed. The heterogeneity of urban structure and function across income levels is discussed.